UK higher education institutions' technology-enhanced learning strategies from the perspective of disruptive innovation - Michael Flavin; Valentina Quintero (Association for Learning Technology, 2018)
The publication of institutional strategies for learning, teaching and assessment in UK higher education is practically ubiquitous. Strategies for technology-enhanced learning are also widespread. This article examines 44 publically available UK university strategies for technology-enhanced learning, aiming to assess the extent to which institutional strategies engage with and accommodate innovation in technology-enhanced learning. The article uses qualitative content analysis as its method, and uses the categories of disruptive innovation, sustaining innovation and efficiency innovation to evaluate individual institutional strategies. The article argues that sustaining innovation and efficiency innovation are more commonplace in the strategies than disruptive innovation, a position which is misaligned with the technology practices of students and lecturers.